One World, Big Screen : Hollywood, the Allies, and World War II - Bennett, M. Todd (Book collections on Project MUSE., 2012)
World War II coincided with cinema's golden age. Movies now considered classics were created when all sides in the war were coming to realize the great power of popular films to motivate the masses. Through multinational research, this book reveals how the Grand Alliance - Britain, China, the Soviet Union, and the United States - tapped Hollywood's impressive power to shrink the distance and bridge the differences that separated them. The Allies, it shows, strategically manipulated cinema in an effort to promote the idea that the UN was a family of nations joined by blood and affection.